1994
DOI: 10.2307/3283414
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Affects Nitric Oxide Production by Murine Peritoneal Macrophages

Abstract: Macrophages from mice that are infected with various intracellular pathogens including Leishmania major, Trypanosoma cruzi, and Salmonella typhimurium are stimulated to produce large quantities of nitric oxide (NO). Both viable and heat-treated L. major amastigotes have been shown to be effective co-signals for NO production in vitro. NO produced by macrophages has anti-microbial and immunosuppressive functions in an immune response. We have shown previously that NO plays a complicated role in T. cruzi infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…T. cruzi I parasites and strains isolated from wild reservoirs or triatomines showed the greatest suppression of NO production. These results are in agreement with reports by other authors 36,38 that T. cruzi has developed strategies to evade NO-mediated anti-microbial activity by suppressing its production. The ability of T. cruzi I parasites to escape from NO is in agreement with other biological characteristics of this genetic group, which include its greater infectivity, rate of intracellular replication, and virulence 23,39,47 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…T. cruzi I parasites and strains isolated from wild reservoirs or triatomines showed the greatest suppression of NO production. These results are in agreement with reports by other authors 36,38 that T. cruzi has developed strategies to evade NO-mediated anti-microbial activity by suppressing its production. The ability of T. cruzi I parasites to escape from NO is in agreement with other biological characteristics of this genetic group, which include its greater infectivity, rate of intracellular replication, and virulence 23,39,47 .…”
Section: Discussionsupporting
confidence: 93%
“…This difference in behavior may also be a consequence of the isolated behavior of G1 (wild reservoir) and A21A, N914A and N120B (bugs) strains, which displayed significantly higher PI values than the others in the T.cruzi I group. In the case of strain A21A, it was shown that it is a mixture (Tc I+Tc II), in contrast to samples N914A and N120B, which are pure Tc I 36 . In another article from our group (in publication 2 ), using the rRNA gene analysis (24Sα) and mitochondrial DNA (subunit 2 of cytochrome oxidase gene -COII) we found that the G1 strain also belongs to the T. cruzi I group.…”
Section: Discussionmentioning
confidence: 93%
“…31 , Toxoplasma gondii 32 and fixed T. cruzi. 33 NO production by macrophages of control group decreased in presence of parasites, suggesting an inhibitory process. However, this decrease was not observed in macrophages from CA treated group.…”
Section: Nitric Oxide Production In Presence Of Parasitesmentioning
confidence: 83%
“…Alternatively or additionally, NO • -resistant parasite isolates could inhibit NO • production by macrophages, or other killing mechanisms such as ROI. Importantly, it has been shown that M. bovis inhibits NO • -mediated killing by murine macrophages [48], as do Cryptococcus neoformans [49], Trypanosoma cruzi [50], as well, as L. (L.) amazonensis infection [51]. Other studies have reported that amastigote surface enzymes can inhibit NO • production and thereby reduce leishmanicidal activity [52,53].…”
Section: Discussionmentioning
confidence: 99%